ANALISIS PERPUTARAN PIUTANG PADA PT WOM (WAHANA OTTOMITRA MULIARTHA) tbk FINANCE DI BLITAR - Gandung Fitra Pambudi; Ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
This study aims to analyze how much the level of accounts receivable turnover at PT WOM (Wahana Ottomitra Multiartha) Finance Division Blitar in the period April - June 2019. The method of data collection in this study uses library research and field research . This type of research is quantitative descriptive, namely the results of this study are numerical data (numbers), after which it is processed and analyzed for conclusions.The analytical method used for testing accounts receivable in this study uses the receivable turn over (RTO) method, which aims to measure the liquidity and activity of the company's receivables. Average collection period (ACP), which aims to measure the average collection time for sales. The arrears ratio, which aims to find out how much the receivables are due and not yet collected from the number of credit sales made. Billing ratio, which aims to find out how much receivables are collected from the total receivables owned by the company.The results of this study indicate that the accounts receivable turnover rate of PT WOM (Wahana Ottomitra Multiartha) Finance Division of Blitar in April amounted to 15.3 times, May 13.7 times and June 13.1 times which is very good can still be in the set average. that is 15 times, so billing by the company is considered good and successful. The average collection of accounts receivable from the company in April was 24 days, May 26 days and June as many as 28 days. The collection period of this company's receivables is quite good, which is less than the company's average of 48 days, so it can be said that the company is very capable of handling billing on time even before maturity. The arrears ratio of companies experienced ups and downs which in April amounted to 14%, May 15% and June only 10%. Where the highest arrears are found in May which can harm the company because the funds should be able to turn back in fixed cash that is embedded in accounts receivable. The cause of the arrears in May was due to the fact that the month coincided with the month of Ramadan and Idul Fitri as well as the number of National holidays and leave for the month. The billing ratio experienced instability which in April was 86%, May 85% and June 90%. Actually the company is able to collect accounts receivable well, it would be good in certain months the company must find a solution so as not to decrease the billing ratio and have to find solutions and ideas so that the following month the billing ratio increases.Keywords: Receivable Turn Over (RTO), Average Collection Period (ACP), Arrears Ratio, Billing Ratio.